Post-Apartheid Criticism: Perceptions of Whiteness, Homosexuality, and Democracy in South Africa - Loukson, Ives S. (transcript, 2020)
South Africa's post-apartheid narrative is one of democracy and equality – but its flaws run deep, argues Ives S. Loukson. Disclosing prejudices about whiteness, homosexuality and democracy in the »staged society«, he claims the concept of relation as an adequate framework for the embodiment of »profane democracy« understood in Agambian terms. Its fluidity is equated to openness and transparency that are relevant dimensions for profane democracy. A demonstration of literary criticism practiced as a fecund interdisciplinary activity, Loukson's study lays the foundation for post-apartheid criticism different from post-colonial criticism.